2023
DOI: 10.1038/s41586-022-05478-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the axial vector form factor from antineutrino–proton scattering

Abstract: Scattering of high energy particles from nucleons probes their structure, as was done in the experiments that established the non-zero size of the proton using electron beams1. The use of charged leptons as scattering probes enables measuring the distribution of electric charges, which is encoded in the vector form factors of the nucleon2. Scattering weakly interacting neutrinos gives the opportunity to measure both vector and axial vector form factors of the nucleon, providing an additional, complementary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…A comparison of the antineutrino-nucleon charged current elastic cross sections calculated using predictions of AVFF from lattice (PNDME 23 [19]) and neutrino-deuterium analysis [20] with MINERvA measurement [17,42] is presented in Figure 9, which is reproduced from Ref. [18].…”
Section: Comparison Of the Differential Cross-section Using Lattice A...mentioning
confidence: 98%
See 2 more Smart Citations
“…A comparison of the antineutrino-nucleon charged current elastic cross sections calculated using predictions of AVFF from lattice (PNDME 23 [19]) and neutrino-deuterium analysis [20] with MINERvA measurement [17,42] is presented in Figure 9, which is reproduced from Ref. [18].…”
Section: Comparison Of the Differential Cross-section Using Lattice A...mentioning
confidence: 98%
“…The MINERνA experiment [17] has recently shown that the axial vector form factor of the nucleon can be extracted from the charged current elastic scattering process ν µ H → µ + n in which the free proton in hydrogen (H) (part of the hydrocarbon in the target) is converted into a neutron. This opens the door to direct measurements of the nucleon axial vector form factor without the need for extraction from scattering off nuclei, whose analysis involves nuclear corrections that have unresolved systematics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finite-volume results can then be matched to infinite volume 𝑁 → Δ and non-resonant 𝑁 → 𝑁 𝜋 and 𝑁 → 𝑁 𝜋𝜋 amplitudes through generalizations of the Lellouch-Lüscher formula under active development [22][23][24][25][26][27] or used to constrain finite-volume nuclear effective theories. The same variational calculations will result in determinations of nucleon elastic axial form factors, another crucial input needed to reduce uncertainties in neutrino-nucleus cross sections [4,5,9,28,29], with the contributions from 𝑁 𝜋 excited states explicitly removed. This will provide important validation for other current and future methods of removing significant 𝑁 𝜋 excited-state contamination from lattice QCD studies of nucleon axial form factors [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In Lattice 2022, I reported the nucleon isovector vector-and axialvectorcurrent form factors [12] calculated jointly by LHP, RBC, and UKQCD collaborations using the 2+1-flavor dynamical domain-wall fermions lattice-QCD ensemble generated jointly by RBC and UKQCD collaborations. In this "48I" ensemble [13], the lattice spacing is set at about 0.1141(3) fm, and the lattice spatial extent is 48 spacings or about 5.4750 (14) fm. The dynamical strange and degenerate up and down quark mass values are set at their essentially physical values to provide the physical Ω mass and a degenerate pion mass of 0.1392(2) GeV.…”
Section: Introductionmentioning
confidence: 99%